CSS framework alternatives : explore five lightweight alternatives to Bootstrap and Foundation with project examples - Shenoy, Aravind; Prabhu, Anirudh (Apress, 2018)
Learn how to use lightweight CSS framework alternatives to build intuitive websites. This book presents five project examples that use Skeleton, Miligram, UI Kit, Material Design Lite and Susy. This no-nonsense introduction will help you understand the concept of designing interactive websites using these frameworks with ease. Each framework is demonstrated through a practical project in an easy-to-understand manner. Web design is streamlined nowadays thanks to CSS frameworks and, although Bootstrap and Foundation rule the roost with web design, you don't need an exhaustive framework like these for smaller websites. You'll get a glimpse into additional front-end frameworks which basically are pre-prepared packages containing structure of files and folders of HTML and CSS documents (some with JavaScript functions) that help designers and developers build interactive and immersive websites.